New species of genus Neodontobutis (Gobioidei: Odontobutidae) from Khe Khang stream in Pu Mat national park - Khoa, Nguyen Xuan; Duc, Nguyen Huu (Academia Journal of Biology, 2012)
Neodontobutis ngheanensis X. K. Nguyen et D. H. Nguyen sp. nov. (fig. 1,2) Holotype: 60176, SL: 63.8 mm; sampled in Khe Khang stream, Pumat national park, Nghe An province. Paratype: PM060177, SL: 61.8 mm; PM060178, SL: 53.4 mm; PM060179, SL: 60.6 mm vµ PM060180 SL: 49.7 mm. Same data as holotype. Diagnosis: N. ngheanensis is distinguished from other species in genus Neodontobutis by the unique combination of following characters: Lateralline scales 26 -29; branch rays in first dorsal fin: 8. Description: Body cylindrical. Head moderately large. Eyes moderately large. Snout pointed. Mouth oblique, posterior end of maxillary slightly extending beyond vertical of anterior margin of orbit. Gill- opening wide. Both jaws with conical teeth. Tongue margin rounded. Fin: D1 VI; D2 I.9; A 7; P 13 - 14; V I.5. First dorsal fin without filamentous extension and all rays about equal. Second dorsal fin higher than first and rear tips of both second dorsal and anal fins not reaching procurrent rays of caudal fin. Pectoral fin long, longer than pelvic fin. Pelvic fin well separated. Caudal fin short, elliptical. Scales: Lateral line: 26 - 29 (table 1). Body with moderately large ctenoid scale. Predorsal region fully scaled except interorbital region and snout. Opercle with many small and median scales, larger near gill opening. Prepectoral area naked. Head line system: No sensory canals on head. Infraorbital papillae generally as simple longitudinal pattern. Row a longitudinal with a small row. Coloration: Head and body blackish and marmorated. Fin with many black spot rows. Upper corner of gill -opening with a black blotch. Remarks: Neodontobutis ngheanensis nov.sp is more similar to Neodontobutis tonkinensis Mai, 1978 (a species from Vietnam and Laos) than to any species of genus Neodotobutis in China and Vietnam. However, the two species can be distinguished by the following mentioned of features: 1. Lateral line scales; 2. Anal fin ray; 3. Caudal fin ray. Distribution: Neodontobutis ngheanensis X. K. Nguyen et D. H. Nguyen is found in Khe Khang stream in Pu Mat national park. Khe Khang stream belonging to Lam river basin. Etymology: Named for Nghe An province. Habitat: Found in slow flowing streams and swamp.